Examining of the Smartphone Cyberloafing in the Class: Relationship with the Attitude towards Learning and Prevention of Cyberloafing - Alanoglu, Muslim; Karabatak, Songul (Int Soc Technology Education & Science-Istes, 2021)
The purpose of the present study is to determine the relationship between students' smartphone cyberloafing and their attitudes towards learning and also to reveal their opinions about what teachers can do to prevent smartphone cyberloafing. Within the scope of the study, data was collected from 676 students at the education faculty at Firat University in Elazig. In the study, a mixed research pattern was used. The correlation analysis was used to determine the relationship between smartphone cyberloafing and attitudes towards learning. Descriptive analysis and content analysis were used to analyze of views of participants. As a result of the study, it was seen that the smartphone cyberloafing in the class does not have any significant relationship with the nature of learning, but it has negative relations with openness to learning and expectations about learning and positive relations with concerns about learning. It was observed that while attitude towards learning has no significant relationship with browsing-related cyberloafing and interactive cyberloafing, there is a significant and negative relationship between attitude towards learning and entertainment cyberloafing. Also, the benefit or harm of learning usage smartphones varies according to the purpose of usage, and the entertainment cyberloafing in the courses is more harmful than other types of cyberloafing.
Keywords: Smartphone; Cyberloafing; Class; Course; Prevention of cyberloafing